Analisis Faktor pada Keterlambatan Studi Mahasiswa Teknik Industri Universitas Ahmad Dahlan - Nadilla Dzikirna Larasati; Wandhansari Sekar Jatiningrum (Manajemen Pendidikan, 2021)
Accreditation for higher education institutions is an important part for ensuring the quality of institutions. The percentage of graduating on time is one of important assessments in the accreditation of study programs by for Higher Education. However, escalating the number of students in Industrial Engineering Study Program, Universitas Ahmad Dahlan, is not matched by the number of students who can graduate on time. As a result, there is an accumulation for the number of students. Therefore, this research aimed to conduct faktor analysis of study completion delay for students in Industrial Engineering Study Program, Universitas Ahmad Dahlan. Data collection was carried out by distributing questionnaires to Industrial Engineering students who experienced of study completion delay. The questionnaire contained questions related to 9 variabels, named intelligence, interests, talents, relationship with family member, relationship with other students, discipline, and completion of final project. Faktor analysis by using Principal Component Analysis was conducted to determine formed faktors. The result showed there were 2 faktors formed from 8 variabels. The first faktor was Potential and Completion of Final Project with eigen value 3.434 and variance could be explained from this faktor was 43.434%. Meanwhile, the second faktor was the Family and Campus Environment with eigen value 1.015 and variance could be explained from this faktor was 12.685%. Thus, study the National Accreditation Board can determine the appropriate strategy based on the result of faktor analysis.